THE IMPORTANCE OF USING AN INTERDISCIPLINARY APPROACH IN THE TEACHING OF SOCIAL SCIENCES AND HUMANITIES - Mahmudov N.A; Botirova S.Ya. (Scholar Express Journal, 2021)
This article provides a philosophical analysis of the relevance of using an interdisciplinary approach in the teaching of social sciences and humanities. In this article, the author focuses on the interrelationship of philosophy and science.
Keywords: philosophy, science, society, objective knowledge, problem, approach, method, cognition, knowledge, education, pedagogy, interdisciplinary approach